Determination of 1,2,4-trichlorobenzene in aqueous solutions treated with tetramethylammonium-cation-modified birnessite type manganese oxide (TMA-OL-1) by SPME-GC - Tolentino, Elaine Nicolas (Animo Repository, 2005)
The sorption capacity of the synthesized birnessite-type manganese oxide octahedral layer for 1,2,4- Trichlorobenzene increased upon modification of the octahedral layer by exchanging the Na ion with tetramethylammonium ions. The amount of TCB sorbed by Na-OL-1 (5.750mg/g) is less than that of TMA-OL- 1 (8.979mg/g). The application of solid phase microextraction-gas chromatography (SPME-GC) showed a simple method of determining an organic pollutant such as TCB in an aqueous medium without liquid-liquid extraction and trouble-some clean up of sample prior to injection in the gas chromatograph. A linear response and sensitive method allowed quantification of the amount of TCB incorporated in the Na-OL-1 and TMA-OL-1 structures